FOSTERING ARTISTIC CREATIVITY AND PROBLEM-SOLVING SKILLS IN 5TH–7TH GRADE STUDENTS THROUGH VISUAL ARTS EDUCATION - Vosiyeva Aziza To‘xtaqulovna (ILMIY YANGILIKLAR VA INTELLEKTUAL TADQIQOTLAR, 2025)
Abstract: This article examines methods for fostering artistic creativity and problem-solving skills in 5th–7th grade students through visual arts education. The study focuses on project-based learning, collaborative activities, experiential methods, and the use of digital tools to enhance students’ creative thinking. Findings suggest that integrating traditional techniques with innovative approaches helps students develop both artistic competencies and critical problem-solving abilities, contributing to holistic personal and cognitive development.